Indonesia's International Trade Opportunities (Based on 2019 Taiwan Partner Country Case Studies) - Silitonga, Betrix (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2023)
Taiwan began collaborating with Indonesia in 1970. This research aims to analyze opportunities for cooperation between Indonesia and Taiwan using descriptive analysis, namely referring to the identification results of literature studies, scientific studies, theoretical understanding, and information obtained from government websites. During the identification period of the last 10 years (2007-2017), Indonesia's total exports to trading partner countries, namely Taiwan, tended to increase every year, and vice versa, Taiwan's total exports to Indonesia also relatively increased. Indonesia needs to take strategic and proactive policies through efforts to increase the added value and competitiveness of Indonesia's leading sectors and strengthen research cooperation to maximize the absorption of technology transfer from Taiwan.